2019
DOI: 10.1177/0261927x19853317
|View full text |Cite
|
Sign up to set email alerts
|

Language Style Matching in Preschooler–Adult Dyads: Associations with Dyad Familiarity and Children’s Age

Abstract: Language style matching (LSM) offers promise as an unobtrusive measure of synchrony between members of conversational dyads, but no studies have explored key questions related to LSM in developmental context. We examined LSM in young children’s ( N = 87, Mage = 54.63 months) interactions with caregivers versus experimenters, and evaluated links between LSM and expressive vocabulary. LSM was significantly higher among caregiver–child than experimenter–child dyads and was positively associated with children’s ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…We also investigated whether lexical alignment is influenced by conversational partners and observed no difference in the degree of lexical alignment exhibited by the children when interacting with their parents relative to an unfamiliar university student. These findings contrast with previous findings in which younger children (i.e., aged 5 years and below) exhibited more alignment with familiar than unfamiliar partners (e.g., Borelli et al., 2019; Ostashchenko, Deliens, Geelhand, Bertels, & Kissine, 2019; Strapp & Federico, 2000). While there are several potential reasons for these differences, it is possible that, as children get older and are exposed to a wider social circle, they may learn to adapt to the linguistic patterns of the broader community, such as teachers, friends, or strangers, more generally than their primary caregivers.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We also investigated whether lexical alignment is influenced by conversational partners and observed no difference in the degree of lexical alignment exhibited by the children when interacting with their parents relative to an unfamiliar university student. These findings contrast with previous findings in which younger children (i.e., aged 5 years and below) exhibited more alignment with familiar than unfamiliar partners (e.g., Borelli et al., 2019; Ostashchenko, Deliens, Geelhand, Bertels, & Kissine, 2019; Strapp & Federico, 2000). While there are several potential reasons for these differences, it is possible that, as children get older and are exposed to a wider social circle, they may learn to adapt to the linguistic patterns of the broader community, such as teachers, friends, or strangers, more generally than their primary caregivers.…”
Section: Discussioncontrasting
confidence: 99%
“…These studies have been conducted in various conversational settings, such as the home environment (Clark, 2007) and the research laboratory (Schwab & Lew‐Williams, 2016). Additionally, a diverse range of tasks, including toy play (Foushee et al., 2022), interactive games (Leung, Tunkel, & Yurovsky, 2021), and spontaneous conversation (Borelli, Klemfuss, & Hollas, 2019), has been used. Further, children have engaged in interactions with conversational partners who are both familiar (Kunert et al., 2011) and unfamiliar (Girolametto & Weitzman, 2002) to them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Misiek et al (2020) report 'robust evidence of children's ability to engage in multi-level linguistic alignment to adult speech from two years old ' (p. 56). Corpora studies have found child-adult language matching on levels of complexity (Dale & Spivey, 2006;Kunert et al, 2011) and function words (Borelli et al, 2019). This coordination may not apply to all parts of language (e.g.…”
Section: Children Adapt Their Speech In Interactionmentioning
confidence: 99%